2022
DOI: 10.1002/bit.28122
|View full text |Cite
|
Sign up to set email alerts
|

Marine biological macromolecules as matrix material for biosensor fabrication

Abstract: The ocean covers two‐third of our planet and has great biological heterogeneity. Marine organisms like algae, vertebrates, invertebrates, and microbes are known to provide many natural products with biological activities as well as potential sources of biomaterials for therapeutic, biomedical, biosensors, and climate stabilization. Over the years, the field of biosensors has gained huge attention due to their extraordinary ability to provide early disease diagnosis, rapid detection of various molecules and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 139 publications
0
6
0
Order By: Relevance
“…Continuing research on the oceans has revealed a wide range of biomedical materials with excellent properties, and we should continue to optimize the exploration of marine resources to ensure the sustainability of the identified biomedical material production [203]. Fully considering the actual clinical needs and developing novel materials based on the combination of biology and advanced methods, the research on marine biomedical materials will better benefit humankind.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Continuing research on the oceans has revealed a wide range of biomedical materials with excellent properties, and we should continue to optimize the exploration of marine resources to ensure the sustainability of the identified biomedical material production [203]. Fully considering the actual clinical needs and developing novel materials based on the combination of biology and advanced methods, the research on marine biomedical materials will better benefit humankind.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…69 Diatom microalgae also provide an excellent biosensing platform for ultrasensitive detection. 54 Furthermore, biomass-derived materials, such as marine biomaterials 70 and lignin-based polymers, 71 are potential materials to synthesize a cost-effective biosensor as they are low-cost and renewable sources. Using aptamers as receptors is also an excellent choice to extend the shelf-life of biosensors, as they can withstand chemicals and high temperatures.…”
Section: Application Of Biosensors In Smart Farmingmentioning
confidence: 99%
“…Because of their hydrophilicity, strong protein affinity, heavy metal ion chelation, biocompatibility, simplicity of modifying the surface chemical group, low cost, acceptable mechanical characteristics, and simple synthesis procedure, these polysaccharide hydrogels are appealing biomaterials for biosensors. [ 277 ] There is a lot of evidence that polysaccharide‐based hydrogels can be used as immobilized biomaterials to manufacture bioreceptors. [ 278 ] Immobilizing bio receptors on the hydrogel surface can be accomplished by physical absorption, trapping, covalent bonding, crosslinking, and other methods.…”
Section: Applications Of Polysaccharide In Medical Technologymentioning
confidence: 99%